Research of the Method Opportunities of Growing Films Conductance Measurement - Sinkevičius, V. (Elektronika ir Elektrotechnika, 2009)
The methods of the non-invasive conductance measurement of the growing thin films were analyzed using the measurement probe with two contact areas. It was determined, that it is possible to reach the extreme of the signal for the layers from the island stage to the continuous layers, choosing the measurements of the substrate, measurement resistance or configuration. Ill. 10, bibl. 11 (in English; summaries in English, Russian and Lithuanian).